Sistem Informasi Penerimaan dan Pengeluaran Kas pada Usaha Bidang Kuliner: Studi Kasus Sekata Kopi - Zalukhu, Delianus; Hutapea, Marlyna I.; Purba, Eviyanti N. (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2024)
Reducing the time and effort required, a computer-based accounting system can automate many tasks previously done manually, such as recording transactions, producing receipts reports, and cash expenditures. The study aims to design and develop information systems that regulate the receipt and expenditure of cash in the culinary business. By using coffee case studies, this information system is expected to improve the accuracy and efficiency of recording financial transactions as well as making it easier for business owners to track their cash flows in real time. The results of the research show that the information system developed can automate the recording of cash received and issued, making financial reports on a regular basis. The use of this system in coffee markets indicates an improved efficiency of financial management and a positive effect on corporate decision-making processes. Therefore, this cash expenditure and receipt information system can be used as a model for other culinary to improve operational efficiency and financial transparency.